The epidemiology and biologics treatment patterns of juvenile idiopathic arthritis in Taiwan- an 8-year follow-up - Hu, Ya-Chiao; Huang, Yun-Lin; Yiao, Szu-Yu; Lin, Min-Ting; Lin, Fang-Ju; Yang, Yao-Hsu (Frontiers in Immunology, 2025)
BackgroundJuvenile Idiopathic Arthritis (JIA) is the most common chronic arthritis in children, causing significant joint inflammation and complications. This study evaluates the incidence, prevalence, and treatment patterns of JIA in Taiwan, focusing on biologic therapy.MethodsA retrospective observational study utilized data from the National Health Insurance Research Database (NHIRD) for the period 2011-2020. Patients diagnosed with JIA were identified, and the annual incidence and prevalence rates were calculated. Treatment patterns, particularly regarding biologics, were assessed. Subgroup analysis compared patients diagnosed with spondyloarthritis (SpA) versus non-SpA within the JIA cohort.ResultsTwo thousand and thirty-three JIA patients were included. The annual prevalence ranged from 18.0 to 24.2 per 100,000 populations under 16 years old, with an incidence of 5.22 to 6.57 per 100,000. A male predominance was noted (male-to-female ratio: 1.08-1.52:1). The JIA-SpA subgroup comprised 49.2% of the JIA cohort. Compared to Non-SpA patients, the JIA-SpA subgroup showed male predominance (70.7% vs. 44.4%, p<0.0001), later age of onset, and lower biologic use (15.2% vs. 23.1%, p<0.001). Tumor necrosis factor alpha inhibitors were the most used biologics, with a continuation rate of 49.1%. Switching occurred in 13.2% of patients, mostly without interruption within a treatment gap of 60 days. Discontinuation without subsequent biologic therapy was observed in 9.5% of patients, while 28.2% restarted therapy after a treatment interruption of more than 60 days.ConclusionThis study highlights the epidemiological characteristics and treatment patterns for JIA in Taiwan, focusing on biologic therapies. Most patients maintained consistent biologics, with a small proportion able to discontinue them, emphasizing the need for region-specific management strategies.